Comparison of three surgical approaches for thoracolumbar junction (T12-L1) tuberculosis: a multicentre, retrospective study - Zeng, Yanping (BMC Musculoskelet Disord, 2019)
BACKGROUND: The surgical approaches to thoracolumbar junction (T12-L1) tuberculosis were controversial. We aimed to compare the safety and efficacy of three different procedures through a multicentre retrospective study. METHODS: The medical records of thoracolumbar junction tuberculosis patients (n = 177) from January 2005 to January 2015 were collected and reviewed. Forty-five patients underwent anterior debridement and instrumented fusion (Group A), 52 underwent anterior combined with posterior debridement and instrumented fusion (Group B) and 80 underwent posterior-only debridement and instrumented fusion (Group C). Patients with neurological deficit were 10 in Group A, 23 in Group B, 36 in Group C. All patients had a standard preoperative and postoperative anti - tuberculous therapy regimen. Clinical outcomes, laboratory indexes and radiological evaluation of the three groups were compared. Operations at each centre were performed by the respective senior medical teams of the six different hospitals. RESULTS: All three surgical approaches achieved bone fusion and pain relief. Cases with neurological deficits had different degrees of improvement after surgery. The operative time was 330.2 ± 45.4 min, 408.0 ± 54.3 min, 227.9 ± 58.5 min, and the blood loss was 744.0 ± 193.8 ml, 1134.6 ± 328.2 ml, 349.8 ± 289.4 ml in groups A, B and C respectively. The average loss of correction was 5.5 ± 3.7° in group A, 1.6 ± 1.9° in group B, 1.7 ± 2.2° in group C, and the difference between groups except B vs C were of statistically significant (P < 0.05). CONCLUSIONS: For patients with thoracolumbar junction (T12-L1) tuberculosis, the posterior-only procedure is the better than the anterior-only procedure in the correction of kyphosis and maintenance of spinal stability. The posterior-only procedure is recommended because it achieves the same efficacy as combined procedure with shorter operation time, less blood loss and trauma.